Molecular characterization of wild and cultivated pigeonpea (Cajanus spp.) species by microsatellites - HEMAVATHY, A THANGA; KALAIYARASI, R; KAVITHA, S; PREMALATHA, N; DURAISAMY, KAVITHAMANI; VINOTHINI, NEDUNCHEZHIY (The Indian Journal of Agricultural Sciences, 2025)
The primary objective of the current investigation was to use SSR markers to examine the degree of molecular genetic diversity among the 50 cultivated genotypes and five wild species using 17 SSR markers. Seven were monomorphic and 10 markers showed polymorphism. The markers CCB 10, PGM 10, PGM 106, CCM 1538, CCM 1886, CCM 2971, CCM 1263, CCM 0268, CCM 0583, PGM 5 and CCM 1026 showed polymorphism among the genotypes. Microsatellite profiling showed that maximum alleles with amplicon sizes of 150–260 bp. This indicated the effectiveness and higher resolution of such marker systems in detecting molecular diversity. Similar to this, a dendrogram was created using 55 pigeonpea genotypes and highly polymorphic 10 SSR markers which revealed 9 major clusters, ranging from Clusters 1–9, with cluster 6 having the largest number of genotypes (12), and clusters 2, 9 having the smallest number of genotypes (2). This study showed the divergence among pigeonpea genotypes which can be further used in pigeonpea breeding programs. All genotypes involved in this study exhibited a wide range of genetic variability due to different centres of origin,  and different genetic constitutions. The genetic relatedness detected in this study may constitute the foundation for future systematic pigeonpea breeding programmes.